Examination of Physical Fitness Evaluations of Severe Obesity During Junior High School - Abe, Keiko; Mimura, Kanichi; Fujii, Katsunori (European Journal of Applied Sciences, 2022)
Hypotheses on physical fitness and motor ability of obesity have not been clearly proven. To be sure, several papers have been reported, but none of them have gone beyond speculation. In other words, statistically warranted amounts of data on obese people have not been obtained. This study examined physique, physical fitness and motor ability measurements obtained in a large-scale investigation over 7 years (from the 2013 to 2019 academic years) based on the physical fitness improvement action plan of City O The measurement results of children in the second year of junior high school were used. In this study, the wavelet interpolation model was applied specifically to the average value and standard deviation of height, physical strength and motor ability (grip strength, sidesteps, sit-and-reach, sit up, endurance running, 50 m dash, standing long jump, 20 m shuttle run, handball throw) for second year junior high school students. An annual span evaluation chart was then constructed. The height, physical strength, and motor ability of second year junior high school boys and girls judged by the annual span evaluation chart of BMI devised by Fujii [16] were applied to this evaluation chart. As a result, the evaluation of physical fitness and motor ability of the second-year junior high school students derived in this study was not a conjecture. Rather, a clear judgment of "Somewhat poor" or "Poor" in the items except for grip strength, sit-and-reach, and handball throwing was derived, and we suggest that a physical fitness and motor ability evaluation for second year junior high school boys and girls could be established here.